2012
DOI: 10.1111/irv.12026
|View full text |Cite
|
Sign up to set email alerts
|

Lower respiratory tract hemorrhage associated with 2009 pandemic influenza A (H1N1) virus infection

Abstract: Please cite this paper as: Kennedy et al. for the 2009 Pandemic H1N1 Influenza‐Associated Lower Respiratory Tract Hemorrhage Working Group. (2012) Lower respiratory tract hemorrhage associated with 2009 pandemic influenza A (H1N1) virus infection. Influenza and Other Respiratory Viruses DOI: 10.1111/irv.12022. Background  Influenza‐associated lower respiratory tract hemorrhage (LRTH) has been reported in previous pandemics and is a rare complication of seasonal influenza virus infection. We describe patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Acute viral pneumonia with alveolar hemorrhage in humans afflicted by seasonal IAV infections is a catastrophic clinical condition promoting bacterial superinfection and hypoxemic respiratory failure. 55,56 We found striking evolution toward alveolar hemorrhage in sub-lethal infections of DRAGA mice with H1N1/PR8 and H3N2/Aichi viruses. Since it is known that upper and lower respiratory viruses including influenza viruses can suppress host transcription for a number of genes, [57][58][59][60] we questioned whether pulmonary hemorrhage detected in H1N1/PR8-infected DRAGA mice may relate to virus-induced alterations of pro-coagulant processes in their lungs.…”
Section: Discussionmentioning
confidence: 71%
“…Acute viral pneumonia with alveolar hemorrhage in humans afflicted by seasonal IAV infections is a catastrophic clinical condition promoting bacterial superinfection and hypoxemic respiratory failure. 55,56 We found striking evolution toward alveolar hemorrhage in sub-lethal infections of DRAGA mice with H1N1/PR8 and H3N2/Aichi viruses. Since it is known that upper and lower respiratory viruses including influenza viruses can suppress host transcription for a number of genes, [57][58][59][60] we questioned whether pulmonary hemorrhage detected in H1N1/PR8-infected DRAGA mice may relate to virus-induced alterations of pro-coagulant processes in their lungs.…”
Section: Discussionmentioning
confidence: 71%
“…In a special session of the Standing Committee of the National People's Congress of the P.R China on the social impact of environmental problems, Yang Chaofei, vice‐chairman of the Chinese Society for Environmental Sciences revealed that the number of environmental “mass incidents” grew at an average of 29% annually, between 1996 and 2011 (Kennedy, 2012). Similarly, the Chinese Academy of Social Sciences (CASS, 2014) found that environmental pollution triggered half of the “mass incidents” that happened in the country (群体性事件 quntixing shijian) that attracted 10,000 or more participants between 2000 and 2013.…”
Section: Environmental Movements In China and India: A Disregarded Sp...mentioning
confidence: 99%
“…While gas-exchanging alveolar type I epithelial cells can generate an antiviral response, high viral loads can overwhelm this and lead to compromised lung function [87,88]. In some severe cases of influenza virus infection, virus and inflammation were noted in the lower respiratory tract or alveoli, with resulting cellular damage ( Figure 2) [8,9,[11][12][13]89]. Additionally, neutrophils have been implicated in the pathophysiology of alveolar damage following infection with influenza virus [90].…”
Section: Acute Respiratory Distress Syndrome and Lung Damage As A Conmentioning
confidence: 99%
“…Several studies report that in fatal cases of influenza virus infection, increased inflammation, and virus are found in the alveoli [8][9][10][11][12][13]. Disruption of the alveolar region due to viral infection and increased inflammation can contribute to the development of acute respiratory distress syndrome (ARDS), which is a major health concern for children and pregnant women [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%